2021
DOI: 10.3390/ijms22042133
|View full text |Cite
|
Sign up to set email alerts
|

Stationary and Progressive Phenotypes Caused by the p.G90D Mutation in Rhodopsin Gene

Abstract: Mutations in rhodopsin gene (RHO) are a frequent cause of retinitis pigmentosa (RP) and less often, congenital stationary night blindness (CSNB). Mutation p.G90D has previously been associated with CSNB based on the examination of one family. This study screened 60 patients. Out of these 60 patients, 32 were affected and a full characterization was conducted in 15 patients. We described the clinical characteristics of these 15 patients (12 male, median age 42 years, range 8–71) from three families including vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Previous descriptions of AD CSNB revealed no association with myopia, nystagmus, and amblyopia unlike other types of CSNB [ 9 , 10 , 11 , 12 ]. Similar to the Slovenian cohort with AD CSNB caused by RHO variants with 20/20 visual acuity, patient 1 had good visual acuity ( Table 5 ) [ 9 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous descriptions of AD CSNB revealed no association with myopia, nystagmus, and amblyopia unlike other types of CSNB [ 9 , 10 , 11 , 12 ]. Similar to the Slovenian cohort with AD CSNB caused by RHO variants with 20/20 visual acuity, patient 1 had good visual acuity ( Table 5 ) [ 9 ].…”
Section: Discussionmentioning
confidence: 79%
“…Previous descriptions of AD CSNB revealed no association with myopia, nystagmus, and amblyopia unlike other types of CSNB [ 9 , 10 , 11 , 12 ]. Similar to the Slovenian cohort with AD CSNB caused by RHO variants with 20/20 visual acuity, patient 1 had good visual acuity ( Table 5 ) [ 9 ]. Patient 1′s myopia of −3.75 and −3.25 diopters was in the range of average myopia in Taiwan and does not seem related to the diagnosis of AD CSNB ( Table 5 ) [ 13 ].…”
Section: Discussionmentioning
confidence: 79%
“…It is possible that CNGA3 and CNGB3 cause a spectrum of disorders between stationary progressive disease with different rates of progression, where different variants or other cis/trans factors affect disease expression. For example, RHO variants may cause stationary (congenital stationary night blindness) or progressive disease (retinitis pigmentosa) even within the same family [48]. It remains to be answered whether the same is true for CNGA3/CNGB3.…”
Section: Cnga3/cngb3 Retinopathy Is Predominantly a Progressive Diseasementioning
confidence: 99%
“…Most patients with the G90D mutation express normal amounts of rhodopsin, and the structure of the rods is well preserved ( Sieving et al, 1995 ), while others exhibit the typical RP manifestation, in which the loss of rods is accompanied by the subsequent death of the cone cells and blindness ( Berson, 1993 ). A cohort study comprised of 15 patients showed that 20 and 53.3% of patients with the G90D mutation displayed CSNB and classic RP, respectively, with no obvious sex differences ( Kobal et al, 2021 ). Recently, slow retinal degeneration was also found in homozygous G90D transgenic mice ( Colozo et al, 2020 ).…”
Section: Mechanisms Of Rhodopsin-related Retinal Disordersmentioning
confidence: 99%